Understanding Public Sector Innovation from A Local Perspective: Contra War (Contraceptive for Women at Risk) Innovation Study in Malang Regency - Roziqin, Ali; Fajrina, Amaliana Nur (Jurnal Borneo Administrator, 2021)
This research aims to understand public sector innovation from a local perspective with a study of the Contra War (Contraceptive for Women at Risk) innovation study in Malang Regency. This innovation aims to reduce maternal and infant mortality rates. This research used a qualitative study with document analysis. Researchers analysed documents from various sources such as official government reports, government regulations, online media news, scientific literature, and books. The result shows that the Contra War innovation has not significantly reduced maternal and infant mortality, but gradually the Contra-War has reduced maternal mortality index (Angka Kematian Ibu/AKI) cases from 27 in 2019 to 14 cases. Meanwhile, infant mortality rate (Angka Kematian Bayi/AKB as many as 62 people in 2020. Another side, the sustainability of innovation has not gone well because of low participation, innovative organisational capacity, and transformational leadership. Therefore, researchers provide suggestions for increasing public participation, collaborating with third parties, and creating innovative work ecosystems and bureaucratic structures.